Explore Associations between Subjective Well-Being and Eco-Logical Footprints with Fixed Effects Panel Regressions - Xiu Wu; Jinting Zhang; Daojun Zhang (Land, 2021)
As environmental degradations constantly and directly threaten human well-being, it is imperative to explore the environmental impacts on people’s happy life. This research investigates the association between subjective well-being (SWB) and ecological footprints (EF) through space-time fixed effects panel regressions. EF, as a vital indicator of environmentally sustainable development, plays a vital role in ecological balance. SWB determines the subjective quality of life for humanity. EF-related factors and socio-economic indexes referring to GDP, urbanization rate, income, education, health, political stability, and political voice accountability in 101 countries were captured. Compared with ordinary least square (OLS), stepwise regression (SR) and fixed effects panel regression models (FEPR) exhibited good fitness regardless of the cross-section or longitudinal models due to R2 beyond 0.9. The finding also discloses that EF and health were positively significant to SWB, while income was negatively significant to SWB. EF was an invert u-shaped link to SWB, which met the assumption of EKC. This research provided a model-driven quantitative method to address environmental impacts on people’s quality life of happiness, and opened shared doors for further research of carbon balance and circular economy.